Hypocholesteremic Activity Of Cow Urine Ark And Aloe Vera In Poultry - Patel, Anuradha; Sharma, R.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to assess out the hypocholeseteremic activity of Cow urine ark and Aloe vera extract in broilers. A significant decrease was observed in serum cholesterol,triglycerides,total lipids, LDL and VLDL.Significant increase was reported in HDL levels. The study reveals that Cow urine and Aloe vera extract has marked hypolipidemic activity.
Keywords: Serum cholesterol; hypocholeseteremic; triglycerides; LDL; VLDL; HDL